Comparison between MassARRAY and pyrosequencing for CYP2C19 and ABCB1 gene variants of clopidogrel efficiency genotyping. (1st January 2019) - Liu, Juan; Xu, Zesheng; Li, Ya; Dai, Shipeng; Liu, Junying; Pan, Junjun; Jiang, Yang
Abstract: Clopidogrel is one of the most frequently used drugs in patients to reduce cardiovascular events. Since patients with different genetic variations respond quite differently to clopidogrel therapy, the related genetic testing plays a vital role in its dosage and genetic testing related to clopidogrel therapy is currently considered as routine test worldwide. In this study, we aim to use two different methods MALDI-TOF mass spectrometry and pyrosequencing to detect gene variant of CYP2C19 and ABCB1. Six single nucleotides polymorphisms (SNP) within CYP2C19 (*2, *3, *4, *5, *17) and ABCB1 C3435T in 458 Chinese Han patients were determined using both MassARRAY and Pyrosequencing. Sanger sequencing was used for verification. Results of both methods were analyzed and compared. Allele frequencies of each SNP and distribution of different genotypes were calculated based on the MassARRAY and Sanger sequencing results. Both methods provided 100% call rates for gene variants, while results of six samples were different with two methods. With Sanger sequencing as the reference results, MassARRAY generated all the same results. The minor allele frequencies of the above six SNPs were 27.1% (CYP2C19*), 5.9% (CYP2C19*3), 0% (CYP2C19*4), 0% (CYP2C19*5), 1.1% (CYP2C19*17), 40.9% (ABCB1), respectively. MassARRAY provides accurate clopidogrel related genotyping with relatively high cost-efficiency, throughput and short time when compared with pyrosequencing.